PROBLEMS AND PROSPECTS OF DEVELOPMENT OF APITOURISM IN KAZAKHSTAN - Aliyeva Zh. N.; Baiburiyev R. M.; Lorant David D.; Shagyrbay A. S.; Kaliaskarova Z. K (Scientific Journal of Pedagogy and Economics, 2019)
In the modern world, one of the most popular and faster growing types of tourism is apitourism. This is due to the growing interest in this type of tourism from tourists of all ages who want to spend their holidays in the apiary tasting bee products (honey, propolis, royal jelly, etc.); tourists are interested in learning the secrets of the technology for making high-quality honey and products related to it. Apiaries become as excursion objects for tourists. Especially attractive for tourists are the goods in the manufacture of which they personally participated. Apitourism promotes the socio-economic revival of rural areas, ensures the diversification of agricultural production, and creates new jobs. The article discusses the current state of development of apitourism in Kazakhstan, review the problems and prospects for its development. The experience of the development of apitourism in foreign countries is analyzed. In the course of using mental modeling and analysis of scientific literature, using the deductive research method, we were able to identify the resource base for the development of apitourism, and assessed the current state of the beekeeping in Kazakhstan. As the main research method, we conducted a sociological survey of potential consumers of tourist services, during which the advantages of apitourism and the main directions of its development were identified.